Maidu materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986
Four items relating to Maidu languages have been identified in the C. F. Voegelin Papers. They are all in Subcollection II, and consist of some Maidu information in two folders--labeled "Eskimo-Aleutian" and "Miscellaneous languages"--in Series II. Research Notes, Subseries I. Eskimo-Aleutian; a folder containing a comparative vocabulary of California tribes (with words from from Hupa, Wiyot, Karuk, Shasta, Achumawi, Atsugewi, Konkow, Yana, Wintu, Maidu, and Modoc) in Series II. Research Notes, Subseries V. Hokan; and a separate Maidu folder in Series II. Research Notes, Subseries VI. Penutian, including Mayan and Zoque. Researchers might also be interested in the general Penutian entry for the Voegelin Papers.